A perspective on SARS-CoV-2 and community transmission in the top COVID-19 affected nations - Rini Chaturvedi; Jyoti Chhibber-Goel; Sumit Malhotra; Amit Sharma (Inishmore Laser Scientific Publishing Ltd, 2021)
In most countries, during the initial months of the COVID-19 outbreak resources were directed to mitigation measures that prevented severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission from symptomatic individuals. The coverage of the pre-symptomatic and asymptomatic individuals' testing required intensive clinical sampling along with rigorous symptom-based screening. Based on the SARS-CoV-2 transmission, the disease outbreak across nations was divided into four distinct stages: (i) epidemic, (ii) community transmission, (iii) local transmission, and (iv) imported cases. Here we discuss the COVID-19 community transmission stage for the top ten COVID-19 affected nations. Epidemic dynamics and policies implemented to contain the spread of SARS-CoV-2 infection varied globally. Further, the mitigation strategies and related health policies for dealing with the pandemic were based on the stages of transmission of the disease. We suggest that correctly identifying the transmission stage during a pandemic ensures the implementation of mitigation strategies. Thus prompt analysis of the status of COVID-19 transmission stage(s) in any nation seems crucial to direct health policies accordingly.